2022
DOI: 10.3390/polym14010200
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationship in Melt-Spun Poly(hydroxybutyrate-co-3-hexanoate) Monofilaments

Abstract: Poly(hydroxybutyrate-co-3-hexanoate) (PHBH) is a biodegradable thermoplastic polyester with the potential to be used in textile and medical applications. We have aimed at developing an upscalable melt-spinning method to produce fine biodegradable PHBH filaments without the use of an ice water bath or offline drawing techniques. We have evaluated the effect of different polymer grades (mol% 3-hydroxy hexanoate, molecular weight etc.) and production parameters on the tensile properties of melt-spun filaments. PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, neat PHBH presents a Newtonian fluid‐like behavior with low viscosity 42 . The viscosity of PHBH has a strong dependency on its molecular weight, as it was demonstrated by Selli et al, 43 who tested PHBH grades with a molecular weight between 300 and 500 kDa. PHBH X131N presents a molecular weight of 440 kDa, 42 thus explaining the higher values of viscosity observed for SH2, which present a higher percentage of PHBH.…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, neat PHBH presents a Newtonian fluid‐like behavior with low viscosity 42 . The viscosity of PHBH has a strong dependency on its molecular weight, as it was demonstrated by Selli et al, 43 who tested PHBH grades with a molecular weight between 300 and 500 kDa. PHBH X131N presents a molecular weight of 440 kDa, 42 thus explaining the higher values of viscosity observed for SH2, which present a higher percentage of PHBH.…”
Section: Resultsmentioning
confidence: 88%
“…Figure shows the WAXD patterns of one-step-drawing PHBV and PHBH films with IC under different soaking conditions. The drawn film after IC in ice–water, hexane, and air showed spot reflections compared to the WAXD ring diffraction pattern of the undrawn films. , The orientation of reflection of drawn films with IC in ice–water, hexane, or air increased by stretching, and the crystal orientation evaluated from the width in the azimuthal direction of (020) reflection (Table ), indicating that the α-form crystals with 2 1 helix conformation ,, as P­(3HB) crystal form are oriented. It has been reported that P­(3HB) and its copolymer also can observe planar zigzag conformation (β-form) in highly drawn films. ,, In this study, no clearly β-form diffraction was observed because of the low drawn ratio, and the short IC time of only 24 h formed a few microcrystalline nuclei (Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…The drawn film after IC in ice−water, hexane, and air showed spot reflections compared to the WAXD ring diffraction pattern of the undrawn films. 17,19 The orientation of reflection of drawn films with IC in ice−water, hexane, or air increased by stretching, and the crystal orientation evaluated from the width in the azimuthal direction of (020) reflection 19 (Table 3), indicating that the α-form crystals with 2 1 helix conformation 10,20,32 as P(3HB) crystal form are oriented. It has been reported that P(3HB) and its copolymer also can observe planar zigzag conformation (β-form) in highly drawn films.…”
Section: Structure Analysis By Wide-angle X-ray Diffraction and Ftir ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] PHBH has been extensively used to fabricate plastic bags and disposable straws, 8 and has been investigated for fiberization into micrometre-sized fibres using melt-spun blowing. 9,10 Electrospinning, an efficient method for obtaining nonwoven fabrics with nanometre-sized fibres, can also be applied to PHBH, but electrospun nonwoven PHBH fibres exhibit poor mechanical properties. [11][12][13] Fillers such as nanosilica, 14 montmorillonite, 15 carbon nanotubes, 16 and glass fibres 17 have been used to enhance the mechanical characteristics of PHBH.…”
Section: Introductionmentioning
confidence: 99%